Web-Based Offline Game Suit Design: A Model Overview - Indah Purnama Sari; Al-Khowarizmi Al-Khowarizmi; Aulia Jannah; Adila Mawaddah Meuraxa; M. Iqbal Tanjung (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
The rapid development of information and communication technology has made it easier for people to complete work. To keep up with the times in the game world, information technology students learn about the HTML (Hyper Text Mark Up Language), CSS (Cascading Style Sheet), and PHP (Hypertext Preprocessor) programming languages to create website-based games. Using qualitative research methods, IT students create website-based games with the HTML, CSS, and PHP programming languages that can be accessed via the XAMPP localhost. Students can play this Game Suit game with a computer offline. So that with this website-based game it will make it easier for people to access it and do not require storage such as downloading game applications.